KONVERSI KSPPS BMT ANDURING KE KOPERASI SYARIAH - Maidawati Maidawati (Universitas Muhammadiyah Prof Dr Hamka, 2023)
Managers of Islamic financial institutions just confuse the names of sharia cooperatives with BMT such as KJKS/BMT, KPPS/BMT. Thus, the role and function of Islamic financial institutions are inappropriate. The purpose of this article is to analyze the differences between the main functions of sharia cooperatives and BMT with the aim that managers of sharia financial institutions, especially sharia cooperatives, can name their sharia financial institutions according to the roles and functions they carry out. This field research uses primary data obtained through interviews with sharia cooperative managers, customers and Sharia cooperative DPS and observation and documentation, secondary data obtained from articles, books, magazines and other relevant references. The data analysis technique was carried out through analysis of reduction and display and verification and narrated descriptively. The results showed that the merger of the name KSPPS BMT Anduring, namely the merger between sharia cooperatives (KSPPS) and BMT, because the initial funds from this financial institution came from a Padang PEMKO grant of Rp. 30,000,000,- which was intended for BMT capital, so until now the name The BMT is still being used, and this merger of names is not appropriate, because KSPPS BMT Anduring only carries out business functions and does not carry out the social functions of BMT. For this reason, KSPPS BMT Anduring must change the name of its sharia financial institution to KSPPS only or KSPPS Baitul Tamwil Anduring.